Assessment of precipitation events affecting the distribution of drinkable water in the Gran Mendoza area, Argentina - Rivera, Juan Antonio (2022)
In the Mendoza river basin, the occurrence of heavy rainfall events in the summer months causes severe erosion processes, debris flows, and flash floods that modify the turbidity of the Mendoza river. The excess of sediments dragged during the occurrence of these events affects the functioning of the water treatment plants, which causes cuts in the supply of drinking water in the Gran Mendoza area, the fourth most populated city in Argentina. Based on this issue, this paper presents a characterization of precipitation events that affect the distribution of drinking water over the region, considering 13 case studies over the period 2013-2020. High-resolution satellite estimates were used for the quantification of precipitation, which were validated with data from six meteorological stations throughout the basin. Based on a composite analysis considering a set of meteorological variables, two synoptic configurations that favor the occurrence of heavy precipitation were obtained: a mid-troposphere low pressure system off the coast of Chile and a thermal anomaly that generates isolated convection in the valleys of the basin. These results could be used to create early warning systems to improve water resource management.